Investigation of the Effects of "First Managers" on Teachers' Professional Lives According to Different Variables - ESGEN, Esra; ERGÜN, Muammer (Adiyaman University, 2023)
Leadership and education have been two topics that researchers have been interested in for years. Many studies have been conducted, especially on relationship-oriented and task-oriented leadership styles. This study examined the impact of the first school administrator teachers worked with on their future careers. Data was collected through a digital survey that included a leadership style scale developed by researchers and demographic information. Exploratory and confirmatory factor analyses were conducted for the developed scale. Later, data was collected from a different group and confirmatory factor analysis was performed again. The study was conducted on a sample group of 530 individuals. The collected data was analyzed with ANOVA and t-test. The findings showed that 70% of the teachers revealed that their first administrator had an impact on their career. It was found that the impact did not differ based on the leadership style used. In addition, it was revealed that there were differences in how teachers were influenced based on the administrator’s seniority and the educational level of the first school they worked at. The finding that the impact did not differ based on task-oriented and relationship-oriented leadership style is in line with the literature.
Keywords: 4. Education